The new politics of global academic mobility and migration - Dervin, Fred (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2015)
This book brings together recent research on Global Academic Mobility and Migration (GAMM) from a variety of perspectives and contexts. There is now a widespread consensus that most countries and world regions are witnessing GAMM. Bringing together leading scholars from Australasia and Europe, this volume offers readers detailed account of the new politics of such acts of mobility and migration. The following key issues are dealt with: mobility determinants, social injustice, management and administrative problems, as well as teaching-learning challenges. The book invites students, researchers and practitioners to reflect further on the nature of today’s education on the move.